Empowering female inmates at Pontianak correctional facility through e-business training to enhance economic empowerment - Patmawati, Patmawati; Waldan, Raziki; Barriyati, Barriyati (Universitas Sarjanawiyata Tamansiswa, 2025)
The stigma against female inmates presents a significant challenge to their social and economic reintegration post-incarceration. This study explores the empowerment of female inmates at the Pontianak Correctional Facility through e-business training as a means of enhancing their economic independence. The research employs a Participatory Action Research (PAR) approach, involving direct engagement with inmates to assess their needs, develop training modules, and evaluate the program’s effectiveness. The training covers fundamental e-business concepts, digital marketing strategies, financial management, and online store operations. Findings indicate that the program successfully improved participants’ digital literacy, entrepreneurial skills, and confidence in starting online businesses. Furthermore, the training contributed to reducing recidivism risks by equipping inmates with sustainable income-generating skills. Challenges such as limited access to technology and post-release business continuity were identified, emphasizing the need for continued mentorship and institutional support. This study highlights the potential of digital entrepreneurship as a reintegration strategy, advocating for broader implementation in correctional facilities.